The effect of curcumin supplementation on cognitive function: an updated systematic review and meta-analysis - Wang, Wenlong; Zhao, Rui; Liu, Bingzheng; Li, Kelei (Frontiers in Nutrition, 2025)
BackgroundPrevious randomized controlled trials (RCTs) did not draw a consistent conclusion about the effect of curcumin on cognitive function.MethodsWe searched Web of Science, PubMed, Cochrane Library and Embase, and 9 RCTs (including 12 independent comparisons) with 501 subjects were included in the present meta-analysis.ResultsCompared with placebo, supplementation of curcumin significantly improved global cognitive function (SMD, 0.82; 95% CI, 0.19 to 1.45; p = 0.010). A curvilinear dose–response effect was observed, and the optimal dose is 0.8 g/day. Subgroup analysis indicated that the beneficial effect of curcumin on cognition was significant only if duration ≥24 weeks (SMD, 1.15; 95% CI, 0.13 to 2.18; p = 0.027), age of participants ≥60 years (SMD, 1.12; 95% CI, 0.03 to 2.21; p = 0.044), or participants from Asian countries (SMD, 0.96; 95% CI, 0.08 to 1.83; p = 0.032). Otherwise, this effect became non-significant (p > 0.05). Sensitivity analysis by excluding each study one by one or excluding all studies with high risk of bias did not obviously influence the final results. No significant publication bias was observed (P for Begg’s Test and Egger’s test = 0.150 and 0.493, respectively).ConclusionSupplementation of curcumin can effectively improve global cognitive function, and the optimal dose and duration is 0.8 g/day and ≥24 weeks. The beneficial effect of curcumin on cognition is more potent in older and Asian participants than younger and Western ones.